CADASIL or MS? Consider “Red Flags” but Avoid a Misdiagnosis: Case Series of a Concomitant Diagnosis - Emanuele, Morena; Matteo, Lucchini; Carmela, Romano; Simona, Petrucci; Matteo, Tartaglia; Roberta, Morosetti; Antonella, Conte; Chiara, Buscarinu Maria; Silvia, Romano; Marco, Salvetti; Massimiliano, Mirabella; Giovanni, Ristori (Archives of Clinical and Medical Case Reports, 2022)
Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is a monogenic autosome-dominant disease with chronic clinical course. Rarely, CADASIL may present with atypical relapsing-remitting manifestations, cerebral and spinal white matter lesions, mimicking inflammatory CNS disease as multiple sclerosis (MS). The rarely co-occurrence of MS and CADASIL may represent a hard challenging diagnosis even for an expert neurologist. Here, we present a case series of two patients with CADASIL showing MRI pattern overlapping MS. They were the only case of co-occurrence of CADASIL and MS in their own family. Both patients were treated with anti-inflammatory and anti-platelet drugs, mostly with good response. Pathogenic hypothesis highlights that genetic events, related to monogenic disease, may expose CNS antigens with a consequent self-immune attack. In CADASIL, the function of Notch3 receptor showed a consistent interplay with immune system activity. Indeed, certain mutations of Notch3 receptor show abnormal upregulation of specific pro-inflammatory patterns. However, even if it is not possible to determinate if the proinflammatory activity may be promoted by pathogenic mutations in Notch3, the "apparent" difference between MS and “inflammatory CADASIL” could be considered more semantic than etiologic.